select the approximate values of x that are solutions to f(x)=0, where f(x)=-4x^2+6x+9

f(x)=-4x^2+6x+9 0 = -4x^2+6x+9

multiplying by -1 on both sides, we get

0 = 4x^2 - 6x -9

now the solution of this above quadratic equation is

0 = (2x-3)(2x-3) 0 = (2x-3)^2

taking square root on both sides, we get

x = 3/2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up